1990
DOI: 10.1111/j.2044-8341.1990.tb02858.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological aspects of male infertility

Abstract: The aim of this research was to study the effect of suspected infertility on psychological functioning, comparing men who suspect that they are infertile (N = 107) with men who have no such suspicion (N = 30). Infertile men had lower self-esteem, higher anxiety and showed more somatic symptoms than fertile men. The effects of moderating variables on the psychological functioning of the subfertile men were analysed. The findings were that causality of infertility, feelings of hopelessness and global attribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
11

Year Published

1994
1994
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 4 publications
3
42
0
11
Order By: Relevance
“…Male partners among infertile couples experience elevated levels of psychological distress (Dyer et al, 2009). Infertile men had lower self-esteem, higher anxiety, and showed more somatic symptoms than fertile men (Kedem et al, 1990). Gana and Jakubowska (2014) reported that their findings confirmed the predictive effects of infertility-related stress on both emotional and marital distress.…”
Section: Introductionmentioning
confidence: 90%
“…Male partners among infertile couples experience elevated levels of psychological distress (Dyer et al, 2009). Infertile men had lower self-esteem, higher anxiety, and showed more somatic symptoms than fertile men (Kedem et al, 1990). Gana and Jakubowska (2014) reported that their findings confirmed the predictive effects of infertility-related stress on both emotional and marital distress.…”
Section: Introductionmentioning
confidence: 90%
“…Physical pain and complaints are more prominent in this group, which is associated with lower productivity. Loss of hope, depression, and decrease in sexual desires are other manifestations in this population [10].…”
Section: Introductionmentioning
confidence: 99%
“…Kedem et al [10] showed that self-respect and self-esteem is much lower in infertile male compared to normal population and they also suffer of a higher anxiety level. Physical pain and complaints are more prominent in this group, which is associated with lower productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Com relação aos estudos que medem a auto-estima, (Callan, 1987;Kedem et al, 1990;Hynes et al, 1992), encontraram que o escore dos indivíduos inférteis era menor; por outro lado, (Brand, Ross e Van Der Merwe, 1982;Paulson et al, 1988;Edelmann, Connoly e Bartlett, 1994), encontraram níveis normais nesses indivíduos. Greil, Leiko e Porter, 1988;Greil, 1991a;Becker e Nachtigall, 1991).…”
Section: O Stress E a Tecnologia De Reprodução Assistidaunclassified
“…Estes dados estão de acordo com diversos autores, que mostraram que a satisfação sexual e conjugal é tão alta nos indivíduos inférteis (Adler e Boxley, 1985;Link e Darling, 1986;Raval et al, 1987;Dennerstein e Morse, 1988;Downey et al, 1989;Berg e Wilson, 1991), ou mais alta (Callan, 1987;Cook et al, 1989;Downey e Mckinney, 1992), do que os indivíduos férteis, porém a maioria dos estudos que avaliaram a satisfação sexual e conceitos relacionados, encontraram poucas diferenças entre os indivíduos inférteis e outros (Freeman, Garcia e Rickels, 1983;Raval et al, 1987;Daniluk, 1988;Kedem et al, 1990;Downey e Mckinney, 1992 A reprodução assistida aparece como uma alternativa repleta de grandes chances, sendo que nesse momento, não há "espaço" para lidar também com mais uma crise emocional e os esforços se concentram nas questões médicas.…”
Section: Tentativas Anteriores E a Tentativa Atualunclassified